Transcription factor PIF4 controls the thermosensory activation of flowering. - Kumar, S; Lucyshyn, D; Jaeger, K; Alós, E; Alvey, E; Harberd, N; Wigge, P (2012)
Plant growth and development are strongly affected by small differences in temperature. Current climate change has already altered global plant phenology and distribution, and projected increases in temperature pose a significant challenge to agriculture. Despite the important role of temperature on plant development, the underlying pathways are unknown. It has previously been shown that thermal acceleration of flowering is dependent on the florigen, FLOWERING LOCUS T (FT). How this occurs is, however, not understood, because the major pathway known to upregulate FT, the photoperiod pathway, is not required for thermal acceleration of flowering. Here we demonstrate a direct mechanism by which increasing temperature causes the bHLH transcription factor PHYTOCHROME INTERACTING FACTOR4 (PIF4) to activate FT. Our findings provide a new understanding of how plants control their timing of reproduction in response to temperature. Flowering time is an important trait in crops as well as affecting the life cycles of pollinator species. A molecular understanding of how temperature affects flowering will be important for mitigating the effects of climate change.